2022
DOI: 10.3390/s22020657
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-Fast TSP on a CNT Heating Layer for Unsteady Temperature and Heat Flux Measurements in Subsonic Flows

Abstract: In this paper, the authors demonstrate the application of a modified Ru(phen)-based temperature-sensitive paint which was originally developed for the evaluation of unsteady aero-thermodynamic phenomena in high Mach number but short duration experiments. In the present work, the modified TSP with a temperature sensitivity of up to −5.6%/K was applied in a low Mach number long-duration test case in a low-pressure environment. For the demonstration of the paint’s performance, a flat plate with a mounted cylinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Ozawa et al developed a fast-response TSP for studying unsteady aerothermodynamic phenomena on a shock-tube wall, based on (Ru(phen) 3 , which has a short luminescence lifetime of less than 1 µs [219][220][221]. Bitter et al demonstrated the application of a modified Ru(phen)-based ultra-fast TSP on a CNT heating layer for unsteady temperature and heat flux measurements in subsonic flows [222]. Ruthenium terpyridine chloride (Ru(trpy)Cl 2 ) is used very often for measurements under cryogenic conditions [223].…”
Section: Temperature-sensitive Paintsmentioning
confidence: 99%
“…Ozawa et al developed a fast-response TSP for studying unsteady aerothermodynamic phenomena on a shock-tube wall, based on (Ru(phen) 3 , which has a short luminescence lifetime of less than 1 µs [219][220][221]. Bitter et al demonstrated the application of a modified Ru(phen)-based ultra-fast TSP on a CNT heating layer for unsteady temperature and heat flux measurements in subsonic flows [222]. Ruthenium terpyridine chloride (Ru(trpy)Cl 2 ) is used very often for measurements under cryogenic conditions [223].…”
Section: Temperature-sensitive Paintsmentioning
confidence: 99%
“…cntTSP was proposed by Klein et al and was initially used to measure the boundary layer transitions in a transonic flow in a cryogenic wind tunnel test [10][11][12]. In a recent study, Bitter et al applied the cntTSP technique to measure the wake of a cylinder on a flat plate in transonic flow [13]. This study successfully captured the temperature change caused by Kármán vortex shedding at approximately 4300 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…However, such sensors acquire pressure information at a single point, which is insufficient for comprehensive study of a flow field. Pressure-sensitive paint (PSP) has received significant attention as a nonintrusive method for surface pressure measurements [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The luminescent intensity of PSP is sensitive to the partial pressure of oxygen in a test gas due to a photophysical process called oxygen quenching [ 15 ].…”
Section: Introductionmentioning
confidence: 99%